Congenital absence of multiple primary teeth - Shilpa; Mohapatra A; Reddy C; Sivakumar N (Wolters Kluwer Medknow Publications, 2010)
Idiopathic agenesis of primary dentition is very rare. This is a case report of a 2-year and 6-month-old girl child who presented with 14 missing primary teeth. A review of the previous case reports is done and the management of these cases is discussed.